A low temperature coefficient carbonyl ferromagnetic powder core and preparation method thereof

Through the high-energy ball milling and ball milling coating process, the morphology of carbonyl iron powder particles is changed and shape anisotropy is introduced. Combined with phenolic/silicon resin coating agent, the permeability temperature coefficient of the carbonyl ferromagnetic powder core is successfully reduced, the problem of performance deterioration in a wide temperature environment is solved, and the efficient, safe and stable production of the material is achieved.

CN119763971APending Publication Date: 2025-04-04SOUTHWEST INST OF APPLIED MAGNETICS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510063011.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The magnetic permeability of the carbonyl ferromagnetic powder center changes greatly with temperature under a wide temperature environment, causing the center frequency point of the filter to drift and deteriorate performance. The existing technology has complex processes and safety hazards, making it difficult to effectively reduce the permeability temperature coefficient.

Method used

The method of combining high-energy ball milling and ball milling coating is adopted to prepare a low-temperature ferromagnetic powder core with a low temperature coefficient by changing the morphology of carbonyl iron powder particles and introducing shape anisotropy.

Benefits of technology

It significantly reduces the permeability temperature coefficient of the carbonyl ferromagnetic powder core, improves the performance stability of the material under wide temperature conditions, simplifies the process flow, and reduces production costs and safety risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119763971A_ABST
    Figure CN119763971A_ABST
Patent Text Reader

Abstract

The invention discloses a low temperature coefficient carbonyl ferromagnetic powder core and a preparation method thereof, belonging to the technical field of magnetic materials. The preparation method adopts a combination of high-energy ball milling and ball milling coating. The invention has low cost, independently controllable raw materials and low risk. The invention cooperates with high-energy ball milling and ball milling coating processes, and the initial magnetic permeability of the obtained carbonyl ferromagnetic powder core is 9.5-13.5, and the temperature coefficient is 60-70ppm / ℃, which greatly reduces the temperature coefficient of the carbonyl ferromagnetic powder core and improves the performance stability of the material under a wide temperature range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic materials, and in particular to a low temperature coefficient carbonyl ferromagnetic powder core and a preparation method thereof. Background Art

[0002] Carbonyl iron (carbonyl iron is mainly composed of iron) magnetic powder core has the characteristics of high saturation magnetic induction intensity (Bs), high quality factor at high frequency, low temperature coefficient, etc., and is widely used in various components, such as filters, short-wave frequency-different devices, power synthesis modules, etc. In particular, the tuning inductor prepared by carbonyl iron magnetic powder core has become an indispensable component in various short-wave communication equipment.

[0003] With the development of electronic communications, higher requirements are placed on the performance stability of electronic components under extreme conditions, such as wide temperature, humidity and heat. Especially in wide temperature environments, the performance stability of electronic components is particularly susceptible to temperature changes. As the core component of the filter, the carbonyl iron powder core tuning inductor has a temperature coefficient (α μ ) is high, generally 100ppm / ℃~250ppm / ℃. During operation, the magnetic permeability changes greatly with temperature, and the resonant inductance attenuates greatly, causing the center frequency of the filter to drift, resulting in increased insertion loss and standing wave ratio of the device, deterioration of performance, and low working efficiency. In order to solve the problem of poor performance of devices caused by such wide temperature, and to ensure the working efficiency of the filter under wide temperature conditions, it is necessary to reduce the temperature coefficient of the carbonyl iron powder core and improve the temperature stability of the performance of the powder core.

[0004] Chinese patent application CN116092812A discloses a method for preparing carbonyl iron powder magnetic cores. In the invention, the temperature coefficient of magnetic permeability of carbonyl iron powder cores is reduced to 22rpm / ℃ at the lowest. However, the process flow is complicated, and includes particle size grading, phosphoric acid phosphating, drying, insulation coating, granulation, mixing, molding, and segmented (3 to 5 stages) heat treatment. The entire production process takes a long time, and phosphoric acid phosphating is dangerous for mass production. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing a low temperature coefficient carbonyl ferromagnetic powder core to solve the above problems.

[0006] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: a method for preparing a low temperature coefficient carbonyl ferromagnetic powder core, wherein the carbonyl ferromagnetic powder core is composed of two raw materials: carbonyl iron powder and phenolic formaldehyde / silicone resin, wherein the amount of phenolic formaldehyde / silicone resin is 5wt%~10wt% of the weight of the carbonyl iron powder, and is prepared by a combination of high-energy ball milling and ball milling coating.

[0007] As a preferred technical solution, the preparation method specifically comprises the following steps: (1) Ingredients: weigh agate balls and carbonyl iron powder according to a material-ball ratio of 1:2 to 1:4, and then weigh the corresponding phenolic / silicone resin according to the weight of the carbonyl iron powder; (2) High-energy ball milling: pour the agate balls and carbonyl iron powder weighed in step (1) into a ball mill, add anhydrous ethanol accounting for 40-50% of the weight of the carbonyl iron powder, and start ball milling. Set the speed to 200rpm-350rpm and the ball milling time to 3h-7h. High-energy ball milling is mainly used to change the particle morphology of carbonyl iron powder, increase the aspect ratio of particles, introduce shape anisotropy, increase the resistance to magnetic domain rotation, and reduce the influence of temperature changes on magnetic permeability. Therefore, insufficient ball milling speed or insufficient ball milling time will result in poor particle flaking, while excessive ball milling speed or excessive ball milling time will result in severe particle flaking or even breakage, which has an adverse effect on reducing the temperature coefficient of magnetic permeability. (3) Ball milling coating: After high-energy ball milling is completed, add the phenolic formaldehyde / silicone resin weighed in step (1) and continue ball milling; (4) Granulation: drying the powder mixed in step (3), grinding and obtaining granules with a size of 40 to 100 meshes; (5) forming, adding a release agent to the granular material obtained in step (4), mixing evenly, and pressing into a solid annular green body; (6) Heat treatment: placing the green body obtained in step (5) in an oven for heat treatment.

[0008] As a preferred technical solution, the purity of the raw materials used in step (1), step (2), step (3) and step (5) is analytical grade.

[0009] As a further preferred technical solution, in step (1), the size of the agate ball is Φ5 mm.

[0010] As a preferred technical solution, in step (3), the ball milling speed is 50 rpm and the coating time is 1 hour.

[0011] As a preferred technical solution, in step (5), the release agent is selected from zinc stearate or calcium stearate, and the amount added is 0.2wt% of the granular material, and the obtained green density is greater than 4.80 g / cm 3 .

[0012] As a preferred technical solution, in step (6), the heat treatment temperature is 120°C to 140°C, and the insulation time is 3h to 5h.

[0013] The second object of the present invention is to provide a low temperature coefficient carbonyl ferromagnetic powder core prepared by the above method.

[0014] Compared with the prior art, the present invention directly uses high-energy ball milling to replace the particle size grading and phosphoric acid phosphating process, and the subsequent heat treatment adopts a non-segmented method, which is simpler and more efficient. In terms of the magnetic properties of the magnetic powder core, the high-energy ball milling method of the present invention reduces the temperature coefficient of the magnetic permeability of the magnetic powder core while also improving the magnetic permeability.

[0015] Compared with the prior art, the advantages of the present invention are: (1) All required materials are common materials available on the market, and do not contain expensive metal oxides such as nickel oxide and molybdenum oxide. Only common types of carbonyl iron powder are used as raw materials, regular-sized agate balls are used as ball milling media, and several common organic resins such as phenolic resin and silicone resin are used as coating agents. The cost is low, the raw materials are independently controllable, and the risk is low; (2) Through high-energy ball milling, the particle morphology of carbonyl iron powder is changed, the aspect ratio of the particles is increased, shape anisotropy is introduced, the resistance to magnetic domain rotation is increased, and the influence of temperature change on magnetic permeability is weakened; combined with the ball milling coating process, the initial magnetic permeability of the carbonyl ferromagnetic powder core is 9.5~13.5, and the temperature coefficient is 60~70ppm / ℃, which greatly reduces the temperature coefficient of the carbonyl ferromagnetic powder core and improves the performance stability of the material under a wide temperature range. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a process flow chart for preparing the carbonyl ferromagnetic powder core prepared by the present invention; Figure 2 This is a microstructure diagram of the carbonyl ferromagnetic powder after high-energy ball milling of the present invention. DETAILED DESCRIPTION

[0017] The present invention will be further described below in conjunction with the accompanying drawings.

[0018] Example 1

[0019] A method for preparing a low temperature coefficient carbonyl ferromagnetic powder core, the specific steps are: The material-ball ratio is 1:2, carbonyl iron powder is 100g, agate ball is 200g, phenolic resin (purchased from Tianjin Dengta Paint Co., Ltd., brand: F01-36) is 5g, and anhydrous ethanol is 45g. First, add carbonyl iron powder, anhydrous ethanol and agate balls into the ball mill, set the ball mill speed to 250rpm, the ball mill time to 3h, and start high-energy ball milling; after the high-energy ball milling, add phenolic resin, set the speed to 50rpm, and the coating time to 1h; then dry, grind and sieve, take granular materials between 40 mesh and 100 mesh, add 0.2wt% zinc stearate, mix evenly, press into a solid ring-shaped green body, heat treat at 120℃ in a constant temperature oven, and keep warm for 3h to obtain a ring magnetic powder core. Its microstructure is shown in the figure below. Figure 2 As shown; The obtained annular magnetic powder core samples were tested for inductance (L) at different temperatures using a precision impedance analyzer and a high and low temperature test chamber, and the magnetic powder core temperature coefficient was calculated based on the inductance temperature change curve, and the initial magnetic permeability was calculated based on the inductance at room temperature, as shown in Table 1; Table 1 Test data of sample ring prepared in Example 1

[0020] Example 2

[0021] A method for preparing a low temperature coefficient carbonyl ferromagnetic powder core, the specific steps are: The material-ball ratio is 1:3, the carbonyl iron powder is 100g, the agate ball is 300g, the phenolic resin is 5g, and the anhydrous ethanol is 45g. First, the carbonyl iron powder, anhydrous ethanol and agate ball are added to the ball mill together, the ball mill speed is set to 300rpm, the ball milling time is 5h, and high-energy ball milling is started; after the high-energy ball milling is completed, the phenolic resin is added, the speed is set to 50rpm, and the coating time is 1h; then after drying, grinding and sieving, the granular material between 40 mesh and 100 mesh is taken, 0.2wt% zinc stearate is added, mixed evenly, pressed into a solid ring-shaped green billet, heat treated at 120°C in a constant temperature oven, and the insulation time is 3h to obtain a ring magnetic powder core; The ring magnetic powder core samples were tested for inductance (L) at different temperatures using a precision impedance analyzer and a high and low temperature test chamber, and the temperature coefficient of the magnetic powder core was calculated based on the inductance temperature change curve, and the initial magnetic permeability was calculated based on the inductance at room temperature, as shown in Table 2; Table 2 Test data of sample ring prepared in Example 2

[0022] Example 3

[0023] A method for preparing a low temperature coefficient carbonyl ferromagnetic powder core, the specific steps are: The material-ball ratio is 1:4, the carbonyl iron powder is 100g, the agate ball is 400g, the silicone resin (purchased from Wacker Chemical Co., Ltd., brand: REN60) is 5g, and the anhydrous ethanol is 45g. First, the carbonyl iron powder, anhydrous ethanol and agate balls are added to the ball mill together, the ball mill speed is set to 350rpm, the ball milling time is 6h, and high-energy ball milling is started; after the high-energy ball milling is completed, the silicone resin is added, the speed is set to 50rpm, and the coating time is 1h; then after drying, grinding and sieving, the granular material between 40 mesh and 100 mesh is taken, 0.2wt% zinc stearate is added, mixed evenly, pressed into a solid ring-shaped green body, and heat treated at 120°C in a constant temperature oven for 3h to obtain a ring magnetic powder core; The ring magnetic powder core samples were tested for inductance (L) at different temperatures using a precision impedance analyzer and a high and low temperature test chamber, and the temperature coefficient of the magnetic powder core was calculated based on the inductance temperature change curve, and the initial magnetic permeability was calculated based on the inductance at room temperature, as shown in Table 3; Table 3 Test data of sample ring prepared in Example 3

[0024] Comparative Example 1 A method for preparing a carbonyl ferromagnetic powder core, comprising the following specific steps: Weigh 100g of carbonyl iron powder, 5g of phenolic resin (purchased from Tianjin Dengta Paint Co., Ltd., brand: F01-36), and 45g of anhydrous ethanol. Add the carbonyl iron powder, anhydrous ethanol and phenolic resin into a ball mill, set the speed to 50rpm, and the coating time to 1h; then dry, grind and sieve, take granules between 40 mesh and 100 mesh, add 0.2wt% zinc stearate, mix evenly, press into a solid ring-shaped green body, heat treat at 120°C in a constant temperature oven, and keep warm for 3h. That is, compared with Example 1, this comparative example does not perform high-energy ball milling on the carbonyl iron powder, but adopts ordinary ball milling method.

[0025] The ring magnetic powder core samples were tested for inductance (L) at different temperatures using a precision impedance analyzer and a high and low temperature test chamber, and the temperature coefficient of the magnetic powder core was calculated based on the inductance temperature change curve, and the initial magnetic permeability was calculated based on the inductance at room temperature, as shown in Table 4; Table 4 Test data of sample ring prepared in Comparative Example 1

[0026] Comparative Example 2 A method for preparing a carbonyl ferromagnetic powder core, comprising the following specific steps: Weigh 100 g of carbonyl iron powder, 5 g of silicone resin (purchased from Wacker Chemie Co., Ltd., brand: REN60), and 45 g of anhydrous ethanol, add the carbonyl iron powder, anhydrous ethanol and silicone resin into a ball mill, set the speed to 50 rpm, and the coating time to 1 h; then dry, grind and sieve, take granules between 40 mesh and 100 mesh, add 0.2 wt% of zinc stearate, mix evenly, press into a solid ring-shaped green body, and heat treat at 120 ° C in a constant temperature oven for 3 h; That is, compared with Example 3, this comparative example does not perform high-energy ball milling on the carbonyl iron powder, but adopts ordinary ball milling.

[0027] The ring magnetic powder core samples were tested for inductance (L) at different temperatures using a precision impedance analyzer and a high and low temperature test chamber. The temperature coefficient of the magnetic powder core was calculated based on the inductance temperature change curve, and the initial magnetic permeability was calculated based on the inductance at room temperature.

[0028] The test data of the sample ring prepared in Comparative Example 2 are as follows: Table 5 Test data of sample ring prepared in Comparative Example 1

[0029] Comparative Example 3 A method for preparing a low temperature coefficient carbonyl ferromagnetic powder core, the specific steps are: The material-ball ratio is 1:4, the carbonyl iron powder is 100g, the agate ball is 400g, the silicone resin (purchased from Wacker Chemie Co., Ltd., brand: REN60) is 5g, and the anhydrous ethanol is 45g. The carbonyl iron powder, anhydrous ethanol and agate ball are first added to the ball mill together, and three comparative experiments are carried out under the same conditions. The ball milling speeds of the three experiments are set to 200rpm, 250rpm, and 300rpm, respectively, and the ball milling time is 6h. High-energy ball milling begins; after the high-energy ball milling is completed, silicone resin is added, the speed is set to 50rpm, and the coating time is 1h; then after drying, grinding and sieving, the granular material between 40 mesh and 100 mesh is taken, 0.2wt% zinc stearate is added, mixed evenly, pressed into a solid ring-shaped green body, heat treated at 120°C in a constant temperature oven, and the insulation time is 3h to obtain a ring magnetic powder core; That is, compared with Example 3, in this comparative example, the carbonyl iron powder was subjected to high-energy ball milling at different rotation speeds (200 rpm, 250 rpm, and 300 rpm).

[0030] The obtained annular magnetic powder core samples were tested for inductance (L) at different temperatures using a precision impedance analyzer and a high and low temperature test chamber, and the magnetic powder core temperature coefficient was calculated based on the inductance temperature change curve, and the initial magnetic permeability was calculated based on the inductance at room temperature, as shown in Table 6; Table 6 Test data of sample rings prepared in Comparative Example 3 and Example 3

[0031] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a low temperature coefficient carbonyl ferromagnetic powder core, characterized in that: The carbonyl ferromagnetic powder core is composed of two raw materials: carbonyl iron powder and phenolic / silicone resin, wherein the amount of phenolic / silicone resin is 5wt%~10wt% of the weight of the carbonyl iron powder, and is prepared by combining high-energy ball milling and ball milling coating.

2. The method according to claim 1, characterized in that The preparation method specifically comprises the following steps: (1) Ingredients: weigh agate balls and carbonyl iron powder according to a material-ball ratio of 1:2 to 1:4, and then weigh the corresponding phenolic / silicone resin according to the weight of the carbonyl iron powder; (2) high-energy ball milling: pour the agate balls and carbonyl iron powder weighed in step (1) into a ball mill, add anhydrous ethanol accounting for 40-50% of the weight of the carbonyl iron powder, and start ball milling. The speed is set to 200 rpm to 350 rpm, and the ball milling time is set to 3 h to 7 h; (3) Ball milling coating: After high-energy ball milling is completed, add the phenolic formaldehyde / silicone resin weighed in step (1) and continue ball milling; (4) Granulation: drying the powder mixed in step (3), grinding and obtaining granules with a size of 40 to 100 meshes; (5) forming, adding a release agent to the granular material obtained in step (4), mixing evenly, and pressing into a solid annular green body; (6) Heat treatment: placing the green body obtained in step (5) in an oven for heat treatment.

3. The method according to claim 1, characterized in that The purity of the raw materials used in step (1), step (2), step (3) and step (5) is analytical grade.

4. The method according to claim 3, characterized in that In step (1), the size of the agate ball is Φ5 mm.

5. The method according to claim 2, characterized in that: In step (3), the ball milling speed is 50 rpm and the coating time is 1 h.

6. The method according to claim 2, characterized in that In step (5), the amount of zinc stearate added is 0.2wt% of the granular material, and the green density obtained is greater than 4.80 g / cm 3 .

7. The method according to claim 2, characterized in that In step (5), the release agent is selected from zinc stearate or calcium stearate.

8. The method according to claim 2, characterized in that: In step (6), the heat treatment temperature is 120°C to 140°C, and the insulation time is 3h to 5h.

9. A low temperature coefficient carbonyl ferromagnetic powder core obtained by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of carbonyl iron powder soft magnetic core for hundred MHz high frequency

    CN116092812A